2010
DOI: 10.3174/ajnr.a1986
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Acute Nontraumatic Cortical Subarachnoid Hemorrhage

Abstract: SUMMARY:Our aim was to review the etiologic background of isolated acute nontraumatic cSAH. While SAH located in the basal cisterns originates from a ruptured aneurysm in approximately 85% of cases, a broad spectrum of vascular and even nonvascular pathologies can cause acute nontraumatic SAH along the convexity. Arteriovenous malformations or fistulas, cortical venous and/or dural sinus thrombosis, and distal and proximal arteriopathies (RCVS, vasculitides, mycotic aneurysms, Moyamoya, or severe atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
108
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(111 citation statements)
references
References 61 publications
3
108
0
Order By: Relevance
“…Another possible mechanism is venous hypertension and subsequent rupture of dilated, valveless, thin-walled, bridging subarachnoid cortical veins devoid of smooth muscle fibers. 6,7,12,16,17) This mechanism is consistent with previous reports, 17,20) and our study showed that cortical SAH usually occurs in the region adjacent to thrombosed veins or sinuses.…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Another possible mechanism is venous hypertension and subsequent rupture of dilated, valveless, thin-walled, bridging subarachnoid cortical veins devoid of smooth muscle fibers. 6,7,12,16,17) This mechanism is consistent with previous reports, 17,20) and our study showed that cortical SAH usually occurs in the region adjacent to thrombosed veins or sinuses.…”
Section: Discussionsupporting
confidence: 81%
“…One possibility is rupture of venous parenchymal hemorrhagic infarcts into the subarachnoid space. 6,7,12,16) However, none of our 4 patients had findings of hemorrhagic venous infarction on MR imaging or CT. Similarly, intraparenchymal findings of venous hemorrhagic infarction were observed in only one of ten patients with cortical SAH due to CVT.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…6 The exact mechanism of cortical SAH caused by CVT is unknown. One possibility is the rupture of venous parenchymal hemorrhagic infarcts into the subarachnoid space, 15,16 although signs of hemorrhagic venous infarction were not found in our patient. Another possible mechanism is venous hypertension and subsequent rupture of dilated, valueless, thin-walled, bridging subarachnoid cortical veins devoid of smooth muscle fibers.…”
Section: Discussionmentioning
confidence: 56%